Periodontal Regeneration – Intrabony Defects: A Systematic Review From the AAP Regeneration Workshop - Kao, Richard T.; Nares, Salvador; Reynolds, Mark A. (Journal of periodontology (1970), 2015)
Background: Previous systematic reviews of periodontal regeneration with bone replacement grafts and guided tissue regeneration (GTR) were defined as state of the art for clinical periodontal regeneration as of 2002. Methods: The purpose of this systematic review is to update those consensus reports by reviewing periodontal regeneration approaches developed for the correction of intrabony defects with the focus on patient‐, tooth‐, and site‐centered factors, surgical approaches, surgical determinants, and biologics. This review adheres to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) guidelines for systematic reviews. A computerized search of the PubMed and Cochrane databases was performed to evaluate the clinically available regenerative approaches for intrabony defects. The search included screening of original reports, review articles, and reference lists of retrieved articles and hand searches of selected journals. All searches were focused on clinically available regenerative approaches with histologic evidence of periodontal regeneration in humans published in English. For topics in which the literature is lacking, non‐randomized observational and experimental animal model studies were used. Therapeutic endpoints examined included changes in clinical attachment level, changes in bone level/fill, and probing depth. For purposes of analysis, change in bone fill was used as the primary outcome measure, except in cases in which this information was not available. The SORT (Strength of Recommendation Taxonomy) grading scale was used in evaluating the body of knowledge. Results: 1) Fifty‐eight studies provided data on patient, tooth, and surgical‐site considerations in the treatment of intrabony defects. 2) Forty‐five controlled studies provided outcome analysis on the use of biologics for the treatment of intrabony defects. Conclusions: 1) Biologics (enamel matrix derivative and recombinant human platelet‐derived growth factor‐BB plus β‐tricalcium phosphate) are generally comparable with demineralized freeze‐dried bone allograft and GTR and superior to open flap debridement procedures in improving clinical parameters in the treatment of intrabony defects. 2) Histologic evidence of regeneration has been demonstrated with laser therapy; however, data are limited on clinical predictability and effectiveness. 3) Clinical outcomes appear most appreciably influenced by patient behaviors and surgical approach rather than by tooth and defect characteristics. 4) Long‐term studies indicate that improvements in clinical parameters are maintainable up to 10 years, even in severely compromised teeth, consistent with a favorable/good long‐term prognosis.